Electronic media use by children in families of high socioeconomic level and familial factors - Kayiran, Sinan Mahir; Soyak, Güzide; Gürakan, Berkan (The Turkish Journal of Pediatrics, 2010)
The aim of this research was to describe electronic media access and use among children aged 6 months to 15 years and to identify familial factors. Data was collected with a questionnaire from 724 parents of children seen in the pediatric outpatient clinic of a private hospital while they awaited examination. Questions included electronic media ownership at home or in the child's bedroom, household habits of electronic media use, educational and occupational status of parents, smoking and alcohol consumption at home, and family income. The top three electronic media devices present at home were television, computer and DVD. On a typical day, 32% of children watched television for approximately less than 1 hour, 36% for 2 hours and 22% for 3 hours. Mean television viewing time was 1.89 +/- 0.76 hours. Nearly 12% of parents spent less than 30 minutes with their children, whereas 28% spent 1 hour, and 59% more than 1 hour. Older children spent more time watching television than the younger ones. Forty-six percent of children used computer and the internet at home on a typical day. Almost 20% of children also had a television in their bedroom and spent more time watching television than those without a television in their bedroom, and the ratio increased by age (one-fifth of 3-5-year olds, one-fourth of 6-10-year-olds and half of 11-15-year-olds, on average). The present study provides data for the education and counselling of parents about the use of electronic media by children and it will contribute to increasing the awareness and sensitivity of the population by drawing attention to the subject.